Pesquisa de Educação Maker com o uso da Plataforma de prototipagem eletrônica sob a ótica discente - Teles, Ana Letícia Filgueiras (2024)
This paper seeks to relate Maker learning and rapid prototyping tools so that the latter can be added to the teaching and development of students. Initially, it sought to explain the educational theories related to the Maker learning approach, through its history and composition. In addition, the main rapid prototyping tools of the electronic board type were presented, as this type allows the use of active education concepts, theory and practice applied to everyday problems. However, the study focuses on analyzing the development of students who seek this knowledge and understanding their point of view in relation to the subject and Maker learning, with the aim of providing a framework of data to encourage more training aimed at these platforms. To this end, a methodology was proposed, using the Arduino platform as a driver for disseminating prototyping concepts, through extension courses made available to the community. The platform was chosen because it is easy to use and access. For analysis, action research was proposed, with participant observations collected by the researcher during the courses and through a form, observing the students' point of view on the approach, based on the collection of numerical data. This made it possible to examine the students' appreciable opinion of the maker methodology and the content covered in the courses, making it clear that they seek this knowledge not only during their academic training but also in their daily lives.